Pendekatan Maqasid Syariah dalam Pengkajian Pendidikan Anak Usia Dini: Telaah terhadap Perlindungan Hifz Al-‘Aql - Ulfa Malini; Sutrisno Sutrisno; Rani Fitrah Nadillah; Ulfi Hidayatul Auliya (E-JURNAL AKSIOMA AL-ASAS, 2026)
This study aims to analyze the maqasid al-shariah approach in early childhood education with a focus on the protection of intellect (hifz al-'aql). This research employs a qualitative approach using a library research method, drawing on scholarly sources such as journals, books, and relevant academic articles. Data were collected through documentation techniques and analyzed using descriptive qualitative analysis. The findings indicate that maqasid al-shariah can serve as a conceptual foundation for developing holistic early childhood education, encompassing cognitive, moral, social, and spiritual aspects. The concept of hifz al-'aql is understood as an effort to protect and develop children's intellectual abilities from an early age through a conducive learning environment and developmentally appropriate teaching methods. Furthermore, the protection of intellect is highly relevant in early childhood education systems, particularly through play-based learning, exploration, and the integration of Islamic values. Keywords: Maqasid Al-Shariah, Hifz Al-'Aql, Early Childhood Education